Assembly Line Balancing using Heuristic Approaches in Manufacturing Industry - Muhammad Razif, Abdullah Make; M. F. F., Ab Rashid; Muhamad Magffierah, Razali; Manugari, Perumal (Faculty of Mechanical Engineering, Universiti Teknologi MARA (UiTM), Malaysia., 2017)
Assembly Line Balancing (ALB) plays a vital function especially in the production line. The installation of an assembly line is a long-term decision and requires large capital of investments. It is important that such a system is designed and balanced so that it able to work efficiently as possible. Many previous researches have proposed different heuristic approach in optimizing the assembly line. However little attention is given toward simulation analysis as proved of the proposed method. In this paper, a real industrial data of simple ALB problem is optimized and simulated for minimizing the number of workstation. Three proposed heuristics in order to improve the efficiency of the production are reviewed before a discrete simulation approach is used to compare the optimized performance. The anticipated performance of computational result is obtained from the problem comprising the workstation and labour performance output.